Specific glycogen synthase kinase-3 inhibition reduces neuroendocrine markers and suppresses neuroblastoma cell growth - Carter, Yvette M (Landes Bioscience, 2014)
Objective: Neuroblastoma is a common neuroendocrine (NE) tumor that presents in early childhood, with a high incidence of malignancy and recurrence. The glycogen synthase kinase-3 (GSK-3) pathway is a potential therapeutic target, as this pathway has been shown to be crucial in the management of other NE tumors. However, it is not known which isoform is necessary for growth inhibition. In this study, we investigated the effect of the GSK-3 inhibitor AR-A014418 on the different GSK-3 isoforms in neuroblastoma. Methods: NGP and SH-5Y-SY cells were treated with 0–20 μM of AR-A014418 and cell viability was measured by MTT assay. Expression levels of NE markers CgA and ASCL1, GSK-3 isoforms, and apoptotic markers were analyzed by western blot. Results: Neuroblastoma cells treated with AR-A014418 had a significant reduction in growth at all doses and time points (P < 0.001). A reduction in growth was noted in cell lines on day 6, with 10 μM (NGP-53% vs. 0% and SH-5Y-SY-38% vs. 0%, P < 0.001) treatment compared to control, corresponding with a noticeable reduction in tumor marker ASCL1 and CgA expression. Conclusion: Treatment of neuroblastoma cell lines with AR-A014418 reduced the level of GSK-3α phosphorylation at Tyr279 compared to GSK-3β phosphorylation at Tyr216, and attenuated growth via the maintenance of apoptosis. This study supports further investigation to elucidate the mechanism(s) by which GSK-3α inhibition downregulates the expression of NE tumor markers and growth of neuroblastoma.